An exploration of women's experience of taking part in a randomized controlled trial of a diagnostic test during pregnancy: A qualitative study. (2nd October 2019) - Hayes‐Ryan, Deirdre; Meaney, Sarah; Nolan, Caroline; O'Donoghue, Keelin
Abstract: Objective: To explore pregnant women's views of participation in a clinical research trial while pregnant. Design: Prospective nested qualitative cohort study embedded within a national, multi‐site randomized controlled trial of a diagnostic test for preeclampsia: Placental Growth Factor. One‐to‐one in‐depth semi‐structured interviews were undertaken with 19 women who had recently participated in the trial at a single recruiting site. The interviews were conducted in private, recorded digitally and transcribed verbatim. Setting: Single tertiary maternity hospital currently recruiting eligible women onto an on‐going randomized controlled trial (NCT 02881073). Participants: Women who had participated in the PARROT Ireland randomized controlled trial during their recent pregnancy. Methods: Thematic analysis was utilized. Each line of the transcribed interviews was coded into a category by two researchers. The resultant categories were reviewed, and those with similarities were pooled allowing the development of themes. Main Outcome Measures: Women's opinions and experience of participation in a randomized controlled trial of an interventional diagnostic test during their pregnancy. Results: Four major themes were identified as follows: (a) Understanding of preeclampsia, (b) Motivators for clinical trial participation, (c) Barriers to decision making and (d) Influence of PARROT Ireland on pregnancy experience. Conclusions: Women are generally interested and positively inclined to participate in research during pregnancy. The potential of risk is an important consideration for eligible pregnant woman. Information and support by both researchers and clinicians are paramount in aiding women's understanding of a research trial.